Pemberdayaan Kader “Deras Ceria” Kader Cerdas Cegah ibu Hamil Anemia di Desa Glonggong - Kurniawati, Anik (Yayasan Inspirasi El Burhani, 2024)
Abstract Introduction: The role of health cadres as part of the community element is an important factor in increasing social support from the community so that it can improve the quality of life of anemia clients in pregnant women. Cadres are expected to play an active role and be able to encourage, motivate and educate the community. Results of the National Health Indicator System (Siskernas) in 2016 The incidence of anemia in pregnant women in Indonesia is 37.1 (Indonesia, 2016). Based on a survey conducted, data was obtained from 24 pregnant women who attended pregnancy classes in Glonggong village, 13 pregnant women (54%) had Hb <11mg/dL. The community service program offered in the Glonggong Village Area, Gondang District, Sragen Regency is the Empowerment of Cadres